Brain tumor cell line authentication, an efficient alternative to capillary electrophoresis by using a microfluidics-based system. Issue 2 (12th December 2013) - An, Qian; Fillmore, Helen L.; Vouri, Mikaella; Pilkington, Geoffrey J.
Abstract: Background: The current method for cell line authentication is genotyping based on short tandem repeat (STR)–PCR involving coamplification of a panel of STR loci by multiplex PCR and downstream fragment length analysis (FLA), usually performed by capillary electrophoresis. FLA by capillary electrophoresis is time-consuming and can be expensive, as the facilities are generally not accessible for many research laboratories. Methods: In the present study, a microfluidic electrophoresis system, the Agilent 2100 Bioanalyzer, was used to analyze the STR-PCR fragments from 10 human genomic loci of a number of human cell lines, including 6 gliomas, 1 astrocyte, 1 primary lung cancer, 1 lung brain metastatic cancer, and 1 rhabdomyosarcoma; and this was compared with the standard method, that is, capillary electrophoresis, using the Applied Biosystems 3130 xl Genetic Analyzer. Results: The microfluidic electrophoresis method produced highly reproducible results with good sensitivity in sizing of multiple PCR fragments, and each cell line demonstrated a unique DNA profile. Furthermore, DNA fingerprinting of samples from 5 different passage numbers of the same cell line showed excellent reproducibility when FLA was performed with the Bioanalyzer, indicating that no cross-contamination had occurred during the culture period. Conclusion: This novel application provides a straightforward and cost-effective alternative to STR-based cell line authentication. In addition, this application would be of great value for cell bank repositories to maintain and distribute precious cell lines.